Analysis and mitigation of fire and explosion hazards in hospital environments from a biomedical engineering perspective - Ibáñez-Cruz, Augusto Jorge Antonio; Espinoza-Morriberon, Dante; Vergara-Florián, Alejandra Micaela Elena; Algoner, William C. (Frontiers in Built Environment, 2025)
BackgroundHospitals are complex and dynamic facilities that house vulnerable people, medical equipment, and hazardous materials, making them susceptible to fires and explosions with potentially catastrophic effects. This study aims to understand and address fire and explosion risks in hospital environments using biomedical engineering, safety, and fire prevention concepts to develop effective mitigation strategies.Materials and MethodsThe study employed a mixed-methods approach, integrating quantitative and qualitative techniques. Data from an insurance and reinsurance company in Peru were analyzed, and surveys, data analysis, and interviews were conducted. The preferred reporting items for systematic review and meta-analysis (PRISMA) methodology was also applied to conduct a thorough literature review.ResultsThe results revealed the most frequent risk factors in hospital settings and identified the most effective mitigation strategies. Implementing these strategies resulted in a considerable decrease in the incidences of fires and explosions.DiscussionThe research provides a comprehensive explanation of hospital fire and explosion risks and proposes evidence-based strategies to improve the safety. These results underscore the relevance of biomedical engineering in managing risks within hospital settings. Despite certain limitations, the study lays a firm foundation for future research aimed at improving hospital safety.